Pendampingan dan Sosialisasi Penyusunan Risk Management pada KSP “Delta Surya Purnama” - Mas'adah Mas'adah; Cuk Triono Singgih; Siti Musyarofah; Moh. Falikhul Isbah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Cooperatives in order to improve the welfare of their members form a savings and loan unit. However, in its development, the existence of the Jombang branch of the Delta Surya Purnama Savings and Loans Cooperative often experiences loan problems in risk management in the form of bad credit. Based on the problems faced by the management of the Delta Surya Purnama Savings and Loan Cooperative, the purpose of this Community Service activity is to provide socialization and assistance in preparing Risk management on credit management so as to minimize bad credit. The methodology used is carried out in the form of outreach/counseling and assistance in preparing Risk Management for good credit management. The results of Community Service activities are expected to increase the knowledge and skills of the administrators and members of the Jombang branch of the Delta Surya Purnama Savings and Loans Cooperative related to knowledge about risk management. The conclusion from this activity is that the Delta Surya Purnama Savings and Loan Cooperative in order to improve the welfare of members are allowed to run a savings and loan business unit. However, in its development, the Savings and Loans Cooperative often faces bad credit problems caused by the failure of the management who handles credit to collect.